EFEKTIVITAS PROGRAM BANTUAN PRODUKTIF USAHA MIKRO (BPUM) UMKM DI DISKOPERINDAG KABUPATEN SUMEDANG - nabila, nazwa (JRPA - Journal of Regional Public Administration, 2025)
The purpose of this study was to determine the effectiveness of the productive assistance program for micro businesses (BPUM) for MSMEs in DiskoperindagSumedang Regency. The research method used in this study was purposive sampling. With research informants, namely the Secretary of the Service, Head of the MSME Division, Functional Section of Entrepreneurship Development, Functional Section. Data collection techniques used were literature studies and field studies consisting of observation, interviews, and documentation. While the data processing procedures in this study were data reduction, data display, data conclusion drawing/verification and triangulation. Based on the results of the study, it was concluded that the effectiveness of the BPUM UMKM program in the Sumedang Regency Trade and Industry Office has been implemented well, seen from the groups that have been successfully reached, data collection of target groups has been carried out according to what is expected, the time for program socialization has been considered good. However, there are still obstacles faced in the implementation of Micro-Business Productive Assistance in Sumedang Regency, namely, from the program organizers so that there are still deviations, at the time of socialization there is unclear information conveyed, the program targets are not quite right and from the economic aspect the targets run effectively. There are efforts to overcome obstacles in the effectiveness of the Micro-Business Productive Assistance program, namely by conducting socialization carried out by program organizers so that understanding of BPUM UMKM runs optimally, and as much as possible by providing and improving what is inhibiting it.